In-situ formation of holmium oxide in pores of Mesoporous Carbon Nanoparticles as substrates for neutron-activatable radiotherapeutics. (June 2017) - Kim, Junghyun; Luo, Zhi-Xiang; Wu, Yue; Lu, Xiuling; Jay, Michael
Abstract: Radionuclide therapy with nano-sized carriers is a very promising approach to treat various types of cancer. The preparation of radioactive nanocarriers can be achieved with minimum handling using a neutron-activation approach. However, the nanocarrier material must possess certain characteristics such as low density, heat-resistance, high metal adsorption, easy surface modification and low toxicity in order to be useful. Mesoporous Carbon Nanoparticles (MCNs) in which holmium oxide is formed in their pores by a wet-impregnation process are investigated as a suitable material for this application. Holmium ( 165 Ho) has a natural abundance of 100% and possesses a large cross-section for capturing thermal neutrons. After irradiation of Ho-containing MCNs in a neutron flux, 166 Ho, which emits therapeutic high energy beta particles as well as diagnostic low energy gamma photons that can be imaged externally, is produced. The wet impregnation process (16 w/w% Ho loading) is shown to completely prevent the leaching of radioactive holmium from the MCNs without compromising their structural integrity. In vitro studies showed that the MCNs containing non-radioactive holmium do not exhibit toxicity and the same formulation with radioactive holmium ( 166 Ho) demonstrated a tumoricidal effect. Post-irradiation PEGylation of the MCN surfaces endows dispersibility and biocompatibility. Graphical abstract: